INOVASI PEMBELAJARAN PAI (STUDI ANALISIS PROGRAM DIROSAH DALAM UPAYA PEMBENTUKAN KARAKTER SISWA MA FATHUL ULUM PANDANHARUM, GABUS, GROBOGAN) - Siti Robi'ah; Rifqi Muntaqo; Asyhar Kholil (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2021)
Efforts to build character are not limited to transferring good values. But reaching out to how to make these values embedded and integrated in the totality of thoughts and actions. The trick is through the habituation of religious activities and social activities such as the Dirosah MA Fathul Ulum activity which trains students to live in a good society. This activity is like KKN activities in lectures but with a short time. In this study the author uses the type of qualitative research. Data collection techniques used are observation, interviews and documentation. For the data analysis technique, the writer uses the Milles and Hubberman model which consists of 3 stages, namely data reduction, data display and conclusion drawing. Dirosah is carried out by class XII students by giving assignments in groups to serve in the community for 15 days by implementing PAI subjects obtained while studying at MA Fathul Ulum. Such as teaching TPQ / Madin, Kultum, congregational prayers, Tadarus, Simaan, Khataman, Majlis Taklim (Yasinan, Tahlilan, Manaqiban and Barzanji), cleaning villages, cleaning mosques / prayer rooms and distributing takjil. This activity forms a religious character, honesty, tolerance, hard work, creative, friendly/communicative, responsible, environmental and social care.